Transcriptomic meta‐analysis of disuse muscle atrophy vs. resistance exercise‐induced hypertrophy in young and older humans. Issue 3 (5th May 2021) - Deane, Colleen S.; Willis, Craig R.G.; Phillips, Bethan E.; Atherton, Philip J.; Harries, Lorna W.; Ames, Ryan M.; Szewczyk, Nathaniel J.; Etheridge, Timothy
Abstract: Background: Skeletal muscle atrophy manifests across numerous diseases; however, the extent of similarities/differences in causal mechanisms between atrophying conditions in unclear. Ageing and disuse represent two of the most prevalent and costly atrophic conditions, with resistance exercise training (RET) being the most effective lifestyle countermeasure. We employed gene‐level and network‐level meta‐analyses to contrast transcriptomic signatures of disuse and RET, plus young and older RET to establish a consensus on the molecular features of, and therapeutic targets against, muscle atrophy in conditions of high socio‐economic relevance. Methods: Integrated gene‐level and network‐level meta‐analysis was performed on publicly available microarray data sets generated from young (18–35 years) m. vastus lateralis muscle subjected to disuse (unilateral limb immobilization or bed rest) lasting ≥7 days or RET lasting ≥3 weeks, and resistance‐trained older (≥60 years) muscle. Results: Disuse and RET displayed predominantly separate transcriptional responses, and transcripts altered across conditions were mostly unidirectional. However, disuse and RET induced directly inverted expression profiles for mitochondrial function and translation regulation genes, with COX4I1, ENDOG, GOT2, MRPL12, and NDUFV2, the central hub components of altered mitochondrial networks, and ZMYND11, a hub gene of altered translation regulation. A substantial number of genes ( n  = 140) up‐regulated post‐RET in younger muscle were not similarly up‐regulated in older muscle, with young muscle displaying a more pronounced extracellular matrix (ECM) and immune/inflammatory gene expression response. Both young and older muscle exhibited similar RET‐induced ubiquitination/RNA processing gene signatures with associated PWP1, PSMB1, and RAF1 hub genes. Conclusions: Despite limited opposing gene profiles, transcriptional signatures of disuse are not simply the converse of RET. Thus, the mechanisms of unloading cannot be derived from studying muscle loading alone and provides a molecular basis for understanding why RET fails to target all transcriptional features of disuse. Loss of RET‐induced ECM mechanotransduction and inflammatory profiles might also contribute to suboptimal ageing muscle adaptations to RET. Disuse and age‐dependent molecular candidates further establish a framework for understanding and treating disuse/ageing atrophy.